Quality Evaluation of Surface Layer in Highly Accurate Manufacturing - Legutko, Stanislaw; Krolczyk, Grzegorz; Krolczyk, Jolanta (Manufacturing Technology Journal, 2014)
Precise characterization of surface topography is very important in many engineering industries. This paper describes potential possibilities of using optical 3D (three dimensional) measurement methods in surface metrology. Surface integrity describes the status and attributes of the machined surface. This paper presents possibilities of using and measurements of surface integrity, namely the surface topography and the physical parameters of which are analysis of microstructure and microhardness of the surface layer.
Keywords: machining; optical microscopy; surface morphology; topography